EVALUATION OF EFFICIENCY OF CARIES PREVENTION BY STABILIZED FLUORIDE TOOTHPASTES - N. Marchenko (Український стоматологічний альманах, 2015)
Introduction. Laboratory and clinical evaluation of the efficiency of stabilized fluoride toothpastes compared to ones without fluoride to prevent dental caries in students has been conducted. The evaluation of an index of stability in the composition of the fluoride toothpastes, the saturation concentration and prolonged action of ionized fluoride in the composition of the oral fluid has been done.